2009
DOI: 10.1097/01.ogx.0000361378.74763.4b
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Allopurinol During Fetal Hypoxia Lowers Cord Blood Levels of the Brain Injury Marker S-100B

Abstract: Several investigators have hypothesized that outpatient preinduction cervical ripening with nitric oxide donors such as isosorbide mononitrate (IMN) would reduce the elapsed time from hospital admission to delivery and improve women's experience of induction of labor. This double-blind randomized placebo-controlled trial investigated whether vaginal self-administration at home by woman at term would improve the process of induction of labor. The study subjects were 350 nulliparous singleton women with cephalic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 1 publication
1
26
0
1
Order By: Relevance
“…Only 5 other studies in the literature have reported on antenatally administered allopurinol, but none of them have described any effects on the histology of the brain. 18,19,22,23,43 In the present study, therapeutic ranges of allopurinol and its metabolite oxypurinol have shown to be attainable after antenatal maternal treatment with allopurinol, while no adverse side effects were observed. These findings are in line with previous studies in both animals and humans.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Only 5 other studies in the literature have reported on antenatally administered allopurinol, but none of them have described any effects on the histology of the brain. 18,19,22,23,43 In the present study, therapeutic ranges of allopurinol and its metabolite oxypurinol have shown to be attainable after antenatal maternal treatment with allopurinol, while no adverse side effects were observed. These findings are in line with previous studies in both animals and humans.…”
Section: Discussionsupporting
confidence: 48%
“…These findings are in line with previous studies in both animals and humans. 18,22,23,43 Masaoka et al were the first to investigate antenatally administered allopurinol during intermittent umbilical cord occlusion in fetal sheep and described a significantly reduced production of superoxide in the allopurinol-treated animals. 22 This indicates a direct effect of allopurinol in preventing the production of free radicals, in scavenging free radicals once formed, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Голландские исследователи объясняют неоднозначность первых результатов тем, что введение аллопуринола постнатально -слишком поздно для полу-чения клинически значимых антиоксидантных эффектов, поэтому в настоящее время они проводят клиническое исследование, где оцениваются эффекты антенаталь-ного введения препарата [151,152]. Проведенное чуть ранее другими нидерландскими авторами исследование по применению аллопуринола беременными при внутри-утробной гипоксии показало достоверно более низкие концентрации белка S100B -нейромаркера ГИП моз-га -в пуповинной крови новорожденных от матерей, принимавших аллопуринол; клинические исходы пока не оценивались [153]. Еще одно плацебоконтролируемое исследование с участием 60 новорожденных с асфикси-ей было проведено в Турции: аллопуринол назначался новорожденным с рождения в течение 3 дней [154].…”
Section: педиатрическая фармакологияunclassified
“…The authors speculated that drug administration was too late to successfully target the immediate ROS surge after resuscitation. In fact, in a more recent study, the same research group has found that maternal treatment of in utero asphyxiated infants with allopurinol reduced the concentration of the brain injury marker S-100B in infants with therapeutic allopurinol levels [159]. It has been also shown that 95% of cord blood samples had target allopurinol concentrations at the moment of delivery [160].…”
Section: Map-2 Densitymentioning
confidence: 98%